SIX MINUTE WALKING DISTANCE CUT-OFF POINT IN INDONESIAN (MONGOLOID) POPULATION - Nusdwinuringtyas, Nury (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction: Six-minute walk test has been a recommended valid and reliable tool used for functional capacity assessment. American Thoracic Society (ATS) had stated that there are no global standards in interpreting 6-minute walking distance (6MWD) as a one-time measurement of functional assessment, which may be caused by population differences and various 6MWT technique utilized in previous studies. Single time cut off is required to evaluate functional status at the start of a program as a baseline for further follow-up evaluations. It is then a necessity to determine these cut off points in every country/race. Methods: The study was performed on healthy subjects, sedentary lifestyle, age 18-50, Indonesian ethnicity (Mongoloid race). Recorded data were 6 minute walking distance,also body height and weight. Predicted walking distance based on gender is obtained by calculating walk distance, body weight, body height, gender and subject age in Nury?s predicted walk distance formula. Data is analysed with SPSS 20, utilizing independent T-test. Results: As much as 123 subjects (58 males, 65 females) were included in this study. Mean walking distance for males is 581,98 meters, while females are 516,80 meters, and these differences were statistically significant. Walking distance cut off point between gender were compared. In male subjects, actual walking distance were taken as normalif >483 meters, poor if 434-483 meters, and very poor <434 meters. As for female subjects, normal when >442 meters, poor when 405-442 meters, and very poor in distance <405 meters. General percentage cut off point in comparison to predicted walking distance was categorized into normal, poor and very poor subgroups. Normal percentage was >85%, poor when distance is 77-85%, and <77% categorized as very poor. Conclusion: There are varying cut off points for walking distance in both males and females. Percentage cut off point as compared to predicted walking distance were not differentiated between genders.